Comparative Evaluation of Periodontal Ligament-associated Protein-1/Asporin Levels in Periodontal Tissue in Health and Disease - Madhu Priya Manohar; R. Saravana Kumar; Pratebha Balu (Wolters Kluwer Medknow Publications, 2024)
Background: Periodontal ligament-associated protein-1 (PLAP-1)/asporin is an extracellular matrix protein that plays a protective role in the pathogenesis of periodontitis. There is a paucity of information about the association between PLAP-1/asporin and periodontitis in human PDL. Thus, in this study, PLAP-1/asporin levels between participants with healthy periodontium and chronic periodontitis were compared and correlated with periodontal parameters. Materials and Methods: Fifty participants were recruited and divided into 25 in each group: Group 1 (control) and Group 2 (test). Probing pocket depth (PPD) and clinical attachment level (CAL) were recorded. Periodontal ligament (PDL) samples were collected from extracted teeth for estimating PLAP-1/asporin levels using the Human Asporin Enzyme-Linked Immunoassay Kit. Results: A statistically significant difference (P = 0.001) in the PLAP-1/asporin levels was observed between Group 1 and Group 2. A weak negative correlation was observed between PLAP-1/asporin levels and periodontal parameters (PPD and CAL) in both groups. Conclusion: In this study, higher PLAP-1/asporin levels in participants with healthy periodontium highlight the protective role of PLAP-1/asporin in maintaining periodontal homeostasis.